Phubbing in Millennial Generation: Influence of Fear of Missing Out and Self Control - Balqis Permata Hikmah; Soerjantini Rahaju; Taufik Akbar Rizqi Yunanto (Journal of Educational, Health and Community Psychology, 2023)
Millennials were very familiar with the use of smartphones. Excessive use of smartphones could trigger the problem of phubbing behaviour that ignores the interlocutor by focusing more on accessing the applications on his smartphone rather than interacting directly with the individual in front of him. The anxiety of being left behind or unable to receive or update information, called Fear of missing out (FoMO) related to phubbing behaviour. Low self-control was a factor in problematic smartphone use, including phubbing behaviour. This study aimed to see whether there was a relationship between Fear of missing out (FoMO) and self-control in phubbing behaviour in the millennial generation. This research used a quantitative survey with accidental sampling techniques. The number of samples in this study was 400 millennial generations in Indonesia. Data collection techniques are carried out online using Google Forms. The results of data collection were analyzed using multiple regression analysis. The result showed that there was a relationship between fear of missing out (FoMO) and self-control with phubbing behavior (R = 0.584, R2 = 0.341, F = 102.542, p = 0.000, p <0.05). The partial t-test found that the self-control variable affected phubbing behaviour, and the partial t-test found that FoMO also affected phubbing behaviour. Self-control contributed more to phubbing behaviour than FoMO.